Performance Analysis of Industrial Ventilation Systems: A Case Study of Exhaust Fan and Roof Cooling Fan Installations in a Textile Manufacturing Area - noviandani, pradika; Latipah, Yeni; Sari, Marta Hayu Raras Sita Rukmika; Suryaman (Operations Research: International Conference Series, 2025)
This study presents a performance analysis of industrial ventilation systems using exhaust fans and roof cooling fans in a textile manufacturing environment. The research was conducted as a case study in the Preparation and Processing areas of a textile factory located in Cimahi, West Java, Indonesia, under actual operating conditions. Air temperature and relative humidity (RH) were measured and compared with recommended textile industry standards (20–30°C and RH 55–75%). Two mechanical ventilation alternatives were evaluated: an exhaust fan system (1.46 × 1.46 m) and a roof cooling fan system (1.82 × 1.45 m). The results show that areas equipped with exhaust fans exhibited lower indoor temperatures by approximately 2–3°C and more stable RH levels (50–52%) compared to areas without mechanical ventilation, where temperatures reached up to 42°C and RH dropped to 25–30%. Both systems required 0.75 kW per unit, with monthly operating costs ranging from IDR 7–10 million. Volumetric efficiency analysis indicates that exhaust fans achieved 60,000 m³/kWh, while roof cooling fans produced 46,667 m³/kWh, indicating a 28% difference in airflow efficiency. These findings provide empirical evidence on the thermal and energy performance characteristics of industrial ventilation systems in textile production areas.